Peran United Nations Development Programme dalam Membantu Pemerintah Myanmar Menanggulangi Kemiskinan Tahun 2020-2022 - Dwiki Prakarsya; Anastasia Wiwik Swastiwi; Sayed Fauzan Riyadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study describes the role of UNDP in the country of Myanmar in an effort to help overcome the problem of poverty. By providing various assistance in terms of economic, social, and political. In accordance with UNDP's goal of focusing on sustainable development. The method used in this research is descriptive research with a qualitative approach. Secondary Data Sources data collection techniques with observation. In this research, the parties involved are UNDP and the state of Myanmar through humanitarian organization relations. The results of this study indicate that the role played by UNDP is to support the recovery of micro and small businesses, rebuild local village infrastructure including water and energy, provide individual skills especially to improve the quality of human resources.